2022
DOI: 10.3390/ijerph19084561
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Structural Characteristics and Psychometric Properties of the SarQoL® Questionnaire in Different Languages: A Systematic Review

Abstract: Background: Sarcopenia is the gradual and global loss of muscle and its functions. Primary sarcopenia is associated with the typical changes of advanced aging and affects approximately 5–10% of the population. The Sarcopenia and Quality of Life (SarQoL®) questionnaire is composed of 55 items, 22 questions, and is organized into seven domains of quality of life. The main objective of this systematic review was to analyze the structural characteristics and psychometric properties of it, as well as to classify it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…After carefully assessing the psychometric properties of the translated versions of SarQoL based on the COSMIN guidelines [ 20 , 59 ], the authors concluded that the analysed versions have psychometric properties that can be qualitatively classified between good and excellent. They state that SarQoL is valid for assessing the quality of life in people with sarcopenia in different countries [ 44 ]. The authors however regret the absence of content validity measurement across the different validation analyses.…”
Section: Discussion / Expert Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…After carefully assessing the psychometric properties of the translated versions of SarQoL based on the COSMIN guidelines [ 20 , 59 ], the authors concluded that the analysed versions have psychometric properties that can be qualitatively classified between good and excellent. They state that SarQoL is valid for assessing the quality of life in people with sarcopenia in different countries [ 44 ]. The authors however regret the absence of content validity measurement across the different validation analyses.…”
Section: Discussion / Expert Commentarymentioning
confidence: 99%
“…However, this is currently only an assumption based on a small amount of preliminary evidence, and no statistical measure of the sensitivity to change using anchor questions was performed. Second, as highlighted in the systematic review by Martinez-Fernandez [ 44 ], the content validity of SarQoL has rarely been studied so far. Because content validity is a psychometric property recognized by COSMIN, future studies should investigate this property in different populations.…”
Section: Discussion / Expert Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…However, these previous studies used different diagnostic criteria for SO than those recently established by ESPEN/EASO [ 10 ], so it is pertinent to study quality of life in older adults using the new diagnostic criteria for SO as well as the EWGSOP2 criteria [ 2 ]. Moreover, as recommended by Tsekoura et al [ 4 ], such assessments should be undertaken using a specific tool, such as the Sarcopenia and Quality of Life (SarQol) instrument [ 15 ], whose different cross-cultural versions have shown very good structural and psychometric properties in people with sarcopenia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%